Stanovení nikotinové kyseliny a jejích metabolitů pomocí HPLC-MS/MS - Žantová, Kamila; Tvrzická, Eva; Vecka, Marek; Žák, Aleš (Chemické listy, 2015)
Nicotinic acid is a hypolipidemic agent with pleiotropic effects. Its drug form with controlled release leads to pyridine metabolites associated with the risk of hepatotoxicity. The aim of the present study was to introduce a HPLC-MS method for the determination of nicotinic acid, nicotinamide, nicotinuric acid, N-methylnicotin¬amide, nicotinamide 1-oxide, 1-methyl-2-oxo-1,2-dihydro¬pyridine-5-carboxamide, and 1-methyl-4-oxo-1,4-dihydro¬pyridine-5-carboxamide in blood plasma or urine. The method is useful for the monitoring in hypolipidemic the¬rapy. We have compared calibration curves of individual metabolites using Hypercarb (graphite carbon) and Hypersil Silica (silicagel) columns. Both columns gave linear calibration curves for all the mentioned analytes (except for 1-methylnicotinamide) in the concentration range 102000 ng ml1. The calibration curve in blood plasma and urine measured with the Hypersil Silica column was linear in the range 204000 ng ml1 for all the tested analytes. The analysis time was 15 min with the column Hypercarb and 27 min with Hypersil Silica. Biological samples were extracted with sulfonated copolymer N-vinylpyrrolidone divinylbenzene. Reproducibility of the results for biological samples varied between 0.06 % and 19.97 %.
Keywords: kyseliny nikotinové; niacin; Chemistry Techniques, Analytical; Nicotinic Acids; vysokoúčinná kapalinová chromatografie; zdraví dobrovolníci pro lékařské studie; Healthy Volunteers; Humans; lidé; Chromatography, High Pressure Liquid; chemické techniky analytické; Plasma; krevní plazma; tandemová hmotnostní spektrometrie; Niacin; Analytic Sample Preparation Methods; metody pro přípravu analytických vzorků; Tandem Mass Spectrometry